2017
DOI: 10.1080/07317115.2017.1373178
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Latino Values and Cultural Beliefs on Brain Donation: Results of a Pilot Study to Develop Culturally Appropriate Materials and Methods to Increase Rates of Brain Donation in this Under-Studied Patient Group

Abstract: Brain tissue is needed to further knowledge about underlying biological mechanism of neurodegenerative diseases, however it is a sensitive topic. Materials assist with family discussion and facilitate the family's follow-through with BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 20 publications
(17 reference statements)
1
29
0
Order By: Relevance
“…Bilbrey et al (2018) assert that health literacy—the skills to access, read, process, understand, and communicate health related information—regarding brain donation can impact people’s decisions concerning brain donation. Although the health literacy of potential donors and their family members was not measured in any of the 14 included studies, participant knowledge about brain donation clearly varied from low to high.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilbrey et al (2018) assert that health literacy—the skills to access, read, process, understand, and communicate health related information—regarding brain donation can impact people’s decisions concerning brain donation. Although the health literacy of potential donors and their family members was not measured in any of the 14 included studies, participant knowledge about brain donation clearly varied from low to high.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of potential brain donors with healthy brain, Harris et al (2013) explain that their participants understood “the valuable contribution the donated ‘normal’ tissue could make to the understanding of the pathological process” that underlie neurodegenerative disease (Harris et al 2013, p. 1101). In contrast, five studies reported that prior to participation in their study participants had little knowledge about brain donation for research (Bilbrey et al 2018; Boise et al 2017; Harris et al 2013; Jefferson et al 2013; Stevens 1998). This finding is confirmed by broader literature: Garrick et al (2006) write, “brain donation is a less familiar process to most of the population and is probably a more difficult personal decision that requires deliberation and consultation with loved ones” (p. 527).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on brain donation among diverse older adults have largely focused on the identification of barriers to brain donation agreement, not barriers to completed brain autopsies once agreement has been obtained. [6][7][8][9][10]17,18 Potential participant-identified impediments to completed brain autopsies can provide insight into postmortem challenges and can allow for the development and implementation of possible ways to address these perceived impediments to completed brain autopsies beforehand. Older African Americans indicated that a lack of family buy-in at the level of brain donation decision making may impede subsequent completed brain autopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Given the well-documented salient role of family among diverse older adults, family members and other factors may serve as potential impediments to completed brain autopsies for these populations who have agreed to brain donation. 6,8,[17][18][19] To our knowledge, prior studies have not examined possible challenges to subsequent completed brain autopsies among diverse older adults who have agreed to brain donation. The purpose of this article, reporting on research using a qualitative focus group methodology, is to identify perceived impediments to completed brain autopsies among diverse older adults who participate in longitudinal studies on aging and have agreed to brain donation.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a key feature of aging and ADRD research includes the requirement or option of organ donation upon death for a more complete understanding of ADRD, from etiology to potential prevention and treatment. Brain autopsies and resultant examinations of brain tissue from decedents of diverse ethnic and racial backgrounds are essential for generalizability, for representation, and for improvement of ADRD treatment and care for all individuals affected by the disease [32]. Few studies with older Latinxs request organ donation from study participants upon death, and despite per-sistent efforts to increase the participation of older Latinxs in ADRD research, the amount of available brain tissue from Latinxs is limited [33].…”
Section: Introductionmentioning
confidence: 99%